2021
DOI: 10.1007/s11665-021-06392-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al2O3 Nanoparticles and Heat Treatment on the Wear Resistance of Electrodeposited Ni-W/Al2O3 Composite Coatings

Abstract: Al 2 O 3 nanoparticles and heat treatment on the wear resistance of Ni-W/Al 2 O 3 coatings. The wear resistance of as-deposited Ni-W/Al 2 O 3 coatings is obviously improved by incorporation of Al 2 O 3 nanoparticles, which can strongly alleviate the serious plowing during the sliding abrasion. By heat treatment at 300 °C, microhardness and wear resistance of Ni-W/Al 2 O 3 are simultaneously improved. For the Ni-W/Al 2 O 3 coatings heat treated at 700 °C, the grain size increases while the microhardness is bare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 35 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The secondary particle reinforcement in Ni-W alloy matrix will enhance the mechanical and chemical properties. Based on this, some of the earlier studies discussed about Ni-W alloy matrix with different secondary particle reinforcement such as TiN [37][38][39][40], TiO 2 [41], ZrO 2 [42,43], MoS 2 [44], La 2 O 3 [45], CeO 2 [46], CNT [47], diamond [48], SiC [49] and Al 2 O 3 [50][51][52][53].…”
Section: Introductionmentioning
confidence: 94%
“…The secondary particle reinforcement in Ni-W alloy matrix will enhance the mechanical and chemical properties. Based on this, some of the earlier studies discussed about Ni-W alloy matrix with different secondary particle reinforcement such as TiN [37][38][39][40], TiO 2 [41], ZrO 2 [42,43], MoS 2 [44], La 2 O 3 [45], CeO 2 [46], CNT [47], diamond [48], SiC [49] and Al 2 O 3 [50][51][52][53].…”
Section: Introductionmentioning
confidence: 94%
“…The study found that the hardness of the composite coating can reach a maximum of 9.1 GPa. Shi et al [12] prepared Ni-W-Al 2 O 3 nanocomposite coatings and found that the addition of Al 2 O 3 can effectively mitigate wear during sliding friction processes. Therefore, adding ceramic reinforcing phases such as SiC, ZrO 2 , Al 2 O 3 , WC, and TaC [13] to Ni-W coatings can effectively improve the coating properties.…”
Section: Introductionmentioning
confidence: 99%